2016
DOI: 10.7566/jpsj.85.094001
|View full text |Cite
|
Sign up to set email alerts
|

Classical Monte Carlo Study for Antiferro Quadrupole Orders in a Diamond Lattice

Abstract: We investigate antiferro quadrupole orders in a diamond lattice under magnetic fields by Monte Carlo simulations for two types of classical effective models. One is an XY model with Z3 anisotropy, and the other is a two-component φ 4 model with a third-order anisotropy. We confirm that the universality class of the zero-field transition is that for the three-dimensional XY model. Magnetic field corresponds to a Z3 field in the effective model, and under this field, we find that collinear and canted antiferro-q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…For FQ order, we find that the Landau theory permits a cubic anisotropy term, which was previously pointed out within a microscopic theory and classical Monte Carlo study of a lattice model. 39,40 This selects an FQ ordered state which is consistent with experimental results on PrTi 2 Al 20 . 35 On the other hand, AFQ order is generally accompanied by a "parasitic" FQ order due to a cubic term which couples them.…”
Section: Introductionsupporting
confidence: 87%
“…For FQ order, we find that the Landau theory permits a cubic anisotropy term, which was previously pointed out within a microscopic theory and classical Monte Carlo study of a lattice model. 39,40 This selects an FQ ordered state which is consistent with experimental results on PrTi 2 Al 20 . 35 On the other hand, AFQ order is generally accompanied by a "parasitic" FQ order due to a cubic term which couples them.…”
Section: Introductionsupporting
confidence: 87%
“…In fact, it has been reported that a thermal fluctuation drives the reentrant behavior of the AFQ phase without any interactions of field-induced moments. 40) On the other hand, the anisotropy of B Q,C can be explained by that of the energy splitting of the non-Kramers doublet for each field direction. The magnitude of the splitting δ is estimated by the second-order perturbation to be δ [100] > δ [110] .…”
Section: Possible Ground Statesmentioning
confidence: 99%
“…In certain pyrochlore magnets, all-in all-out magnetic order has been proposed to lead to "effective octupoles" on tetrahedra [7]. Ongoing experimental [8-10] and theoretical investigations [11][12][13][14] of PrTi 2 Al 20 and PrV 2 Al 20 have also uncovered quadrupolar and ferro-octupolar orders.Recently, unconventional multipolar orders have also been proposed in d-orbital metals to occur as Pomeranchuk instabilities of spin-orbit coupled Fermi surfaces [15]. Specifically, metallic oxides which have d-orbital ions with large SOC, such as LiOsO 3 and Cd 2 Re 2 O 7 , have been proposed as potential candidates to realize this physics [15].…”
mentioning
confidence: 99%